2013
DOI: 10.1136/bmjopen-2013-003894
|View full text |Cite
|
Sign up to set email alerts
|

Responses to concerns about child maltreatment: a qualitative study of GPs in England

Abstract: ObjectivesTo provide a rich description of current responses to concerns related to child maltreatment among a sample of English general practitioners (GPs).DesignIn-depth, face-to-face interviews (November 2010 to September 2011). Participants selected and discussed families who had prompted ‘maltreatment-related concerns’. Thematic analysis of data.Setting4 general practices in England.Participants14 GPs, 2 practice nurses and 2 health visitors from practices with at least 1 ‘expert’ GP (expertise in child s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 32 publications
0
21
0
5
Order By: Relevance
“…The analyses generated a detailed description of seven GP responses (monitoring, coaching, advocating, opportune healthcare, recording concerns, referring to other professionals and joint-working with other professionals) as well as theory about the types of families for whom they were used and the contexts which facilitated them. These results are published elsewhere [16].…”
Section: Analysing Datamentioning
confidence: 69%
See 4 more Smart Citations
“…The analyses generated a detailed description of seven GP responses (monitoring, coaching, advocating, opportune healthcare, recording concerns, referring to other professionals and joint-working with other professionals) as well as theory about the types of families for whom they were used and the contexts which facilitated them. These results are published elsewhere [16].…”
Section: Analysing Datamentioning
confidence: 69%
“…Health visitors may not themselves receive important information from other agencies: in their overview of a series of studies about safeguarding children in the UK, Ward and Davies reported that heath visitors were just as frustrated as GPs at the lack of feedback from children's social care ( [9], p. 119). Wider interview data from our study also revealed that health visitors may not pass on all relevant information to the GP even if they are aware of it and even if they attend the vulnerable family meeting [16]. Assuming that health visitors know and share relevant information from other agencies might leave GPs erroneously thinking they have the bigger picture and impede good risk assessment and monitoring.…”
Section: Flow Of Meaningful Information Into the Meetingmentioning
confidence: 79%
See 3 more Smart Citations